Expatriate Entrepreneurs in China: An Institutional Theory Perspective - Turner, Benjamin N (2010)
This study looks to increase what is known about the entrepreneurs driving the growth of what is now the second biggest economy in the world. The previously un-researched demographic of expatriate entrepreneurs is explored through an institutional theory perspective. Twelve semi-structured interviews were carried out with entrepreneurs operating in a range of sectors and based in the Chinese cities of Shanghai and Beijing. These in-depth responses gave valuable insights into the institutional setting of China and how it is developing as well as liability of foreignness experienced by the entrepreneurs and how it can be overcome. Finally, the implications for entrepreneurs and theorists are discussed, as well as the avenues for future research.